Acoustic response of a laser-excited polycrystalline Au-film studied by ultrafast Debye–Scherrer diffraction at a table-top short-pulse x-ray source - W. Lu; M. Nicoul; U. Shymanovich; F. Brinks; M. Afshari; A. Tarasevitch; D. von der Linde; K. Sokolowski-Tinten (AIP Advances, 2020)
The transient acoustic response of a free-standing, polycrystalline thin Au-film upon femtosecond optical excitation has been studied by time-resolved Debye–Scherrer x-ray diffraction using ultrashort Cu Kα x-ray pulses from a laser-driven plasma x-ray source. The temporal strain evolution has been determined from the transient shifts of multiple Bragg diffraction peaks. The experimental data are in good agreement with the results of calculations based on the two-temperature model and an acoustic model assuming uniaxial strain propagation in the laser-excited thin film.